Pengaruh Terapi Back Massage terhadap Intensitas Nyeri pada Lansia dengan Osteoarthritis di Puskesmas Deleng Pokhisen - Gordon H Aritonang; Anisah Anisah (Universitas Malahayati, 2023)
ABSTRACT Osteoarthritis is a disease that ranks 3rd out of the 10 highest diseases. The prevalence of osteoarthritis in Aceh at 13.26% is the highest in Indonesia based on the results of the 2018 Basic Health Research. Pain, stiffness and difficulty moving the legs are the most commonly felt symptoms. Pain when moving the foot will hinder the sufferer in carrying out their daily activities. Analgesics and non-steroidal anti-inflammatory drugs are therapies to relieve pain. Non-pharmacological therapy to reduce pain can be used, one of which is Back Massage therapy (Slow-Stroke Back Massage). The purpose of this study was to determine the effect of Back Massage therapy on pain intensity in the elderly with osteoarthritis at the Deleng Pokhisen Health Center. This type of research is a quasi-experimental research design with a posttest only control design. This research was conducted on March 22-28 2022. The population was all elderly people with osteoarthritis who were treated at the Deleng Pokhisen Aceh Tenggara Health Center. The total sample of 16 respondents was taken by means of purposive sampling. The results showed that the average pain intensity in the intervention group was 2.13 and in the control group was 3.88. The results of the independent t-test statistical test obtained a p value = 0.001 (p ≤ 0.05), meaning that there is an effect of Back Massage therapy on pain intensity in the elderly with osteoarthritis at the Deleng Pokhisen Health Center. It is hoped that the Deleng Pokhisen Health Center can provide education on Back Massage therapy as a non-pharmacological treatment for osteoarthritis sufferers. Keywords: Osteoarthritis, Pain Intensity, Back Massage Therapy ABSTRAK Osteoarthritis merupakan suatu penyakit yang menduduki peringkat ke 3 dari 10 penyakit tertinggi. Prevalensi osteoarthritis di Aceh sebanyak 13,26% adalah jumlah tertinggi di Indonesia berdasarkan hasil Rikesdas Tahun 2018. Nyeri, rasa kaku dan sulit menggerakkan kaki merupakan gejala paling banyak dirasakan. Nyeri saat menngerakkan kaki akan menghambat penderita dalam melaksanakan aktifitasnya sehari-hari. Analgesik dan obat antiinflamasi non steroid merupakan terapi untuk menghilangkan rasa nyeri. Terapi non farmakologi untuk mengurangi rasa nyeri dapat digunakan, salah satunya dengan terapi Back Massage (Slow-Stroke Back Massage). Tujuan dari penelitian ini adalah untuk mengetahui pengaruh terapi Back Massage terhadap intensitas nyeri pada lansia dengan osteoarthritis di Puskesmas Deleng Pokhisen. Jenis penelitian ini adalah quasi eksperimen dengan rancangan penelitian posttest only control design. Penelitian ini dilaksanakan pada tanggal 22-28 Maret 2022. Populasi adalah semua lansia dengan osteoarthritis yang berobat di Puskesmas Deleng Pokhisen Aceh Tenggara. Jumlah sampel 16 responden yang diambil dengan cara purposive sampling. Hasil penelitian menunjukkan rata-rata intensitas nyeri pada kelompok intervensi adalah 2.13 dan pada kelompok kontrol adalah 3.88. Hasil uji statistik t-test independen didapatkan nilai p value = 0,001 (p ≤ 0,05), berarti ada pengaruh terapi Back Massage terhadap intensitas nyeri pada lansia dengan osteoarthritis di Puskesmas Deleng Pokhisen. Diharapkan pihak Puskesmas Deleng Pokhisen dapat memberikan edukasi terapi Back Massage sebagai salah satu pengobatan non farmakologi pada penderita osteoarthritis. Kata Kunci: Osteoarthritis, Intensitas Nyeri, Terapi Back Massage